Effect of hybrid rice varieties on growth and development of broilers and ducks - Frederick M. LeMieux; Courtney P. Villemarette; Eddie K. Lyons; Thomas H. Shields; Norman German (Animal Nutrition, 2021)
Three experiments (Exp. 1, n = 144 broilers [Ross × Ross]; Exp. 2, n = 118 mallard ducklings [Anas platyrhynchos]; and Exp. 3, n = 75 mature mallard ducks) were conducted to determine the effects of 3 levels of unmilled hybrid rice on growth performance and organ and gastrointestinal tract development. The dietary treatments were 1) corn-soybean meal (basal), 2) basal + 5% hybrid rice, and 3) basal + 10% hybrid rice for Exp. 1 to 3, respectively. One bird from each pen in Exp. 1 (n = 24) and all the birds in Exp. 2 (n = 118) and Exp. 3 (n = 75) were randomly selected and euthanized to determine linear measurements and organ and gastrointestinal tract weight. In Exp. 1 and 2, birds fed 10% rice experienced slower growth (P < 0.05) than birds fed the basal diet. In Exp. 3, the addition of rice did not affect growth performance. Rice addition did not affect organ length or weight (P > 0.05) in Exp. 1. However, birds fed 5% rice had significantly increased (P < 0.05) pancreas, ileum, and jejunum weights in Exp. 2, and 10% rice significantly increased (P < 0.05) liver weight in Exp. 3. The addition of 10% unmilled rice to broiler and duck diets may reduce growth performance.